2021
DOI: 10.1002/ctpp.202100153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trapped ions concentration on the dynamics of dust‐acoustic periodic travelling waves in dusty plasmas

Abstract: This study is essentially an attempt to investigate the effects of trapped ions concentration on the dynamics of dust‐acoustic (DA) periodic travelling waves in dusty plasmas, which consist of dust fluid, trapped ions, and Maxwellian electrons. The physical nature of DA solitary and periodic travelling waves in the plasma model at hand is governed by a Korteweg‐de Vries (KdV) type equation. Bifurcation analysis of the Hamiltonian system is applied to demonstrate the probability of the presence of DA solitary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…[ 23 ] Since then, several works have been devoted to studying the different acoustic modes in plasma media in the presence of trapped particles. [ 21–28 ] During the last two decades, the notion of particle trapping has been generalized to the case of non‐Maxwellian plasmas. [ 29–34 ] For example, Aoutou et al, [ 30 ] have investigated DA solitons in a plasma consisting of nonthermal‐superthermal‐trapped ions and suprathermal electrons.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Since then, several works have been devoted to studying the different acoustic modes in plasma media in the presence of trapped particles. [ 21–28 ] During the last two decades, the notion of particle trapping has been generalized to the case of non‐Maxwellian plasmas. [ 29–34 ] For example, Aoutou et al, [ 30 ] have investigated DA solitons in a plasma consisting of nonthermal‐superthermal‐trapped ions and suprathermal electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Again, it is observed that the theoretical results and predictions may vary from the experimental results [27,28]. To make an improvement, researchers used the reductive perturbation method [29][30][31] in a wide range including the higher-order nonlinear and dissipative terms that give an inhomogeneous differential equation. They took the aid of Abel's theorem and the variation of parameter method to analyze such equations.…”
Section: Introductionmentioning
confidence: 99%